The isolation of differentially expressed genes in fibroblast growth factor stimulated BC3H1 cells by subtractive hybridization - Li, W B (BioTechniques, 1994)
We have developed a subtractive hybridization procedure based on the hybridization of a single-stranded phagemid cDNA library (target) to biotinylated RNA (driver). We have applied this method to fibroblast growth factor (FGF) induced-uninduced mouse brain tumor-derived muscle-like cell. BC3Hl cDNA libraries. After hybridization to a C(o)t value of 1000, cDNAs common to the target and driver populations were subtracted up to 231-fold, whereas several highly induced genes were enriched from 2-15-fold. Interestingly, moderately induced genes (e.g., the 12-fold-induced nur/77 gene) were subtracted even at a low C(o)t value of 50. Therefore, at every C(o)t tested, subtractive hybridization tended to equalize the uninduced and moderately induced common sequences within target populations regardless of the abundance of the gene species. These observations suggest that subtractive hybridization should only be used for identifying target genes that are either uniquely expressed or highly induced